Hyperfine transition in 209Bi80+—one step forward. (26th November 2015) - Sánchez, R; Ullmann, J; Vollbrecht, J; Andelkovic, Z; Dax, A; Geithner, W; Geppert, Ch; Gorges, Ch; Hammen, M; Hannen, V; Kaufmann, S; König, K; et al.
Abstract: The hyperfine transitions in lithium-like and hydrogen-like bismuth were remeasured by direct laser spectroscopy at the experimental storage ring. For this we have now employed a voltage divider which enabled us to monitor the electron cooler voltage in situ . This will improve the experimental accuracy by about one order of magnitude with respect to our previous measurement using the same technique.